2015
DOI: 10.1016/j.clinthera.2015.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and tolerability study of artemisinin-piperaquine combination (ArtequickR) versus artemeter-lumefantrine (Co-ArtemR) for the treatment of uncomplicated plasmodium falciparum T Malaria in Ijebu ode local government health services in Nigeria

Abstract: August 2015 e9(acute on chronic liver failure). Twelve ADRs were considered due to a single drug, 10 to multiple drugs, and 5 to traditional medicines. In one patient a metabolic drug interaction with fluconazole was implicated. In 6 cases, drugs considered exacerbated prior disease. Conclusions: We were effective in improving ADR reporting, identifying important contributions of ADRs to serious morbidity, and identifying preventable patterns of ADRs. Prior similar ADRs, drugdisease interactions, and tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Our initial search found 45 relevant articles published between 2000 and 2020, of which 9 reported repetitive data. After screening for titles, 38 abstracts, and 15 full-text reviewed, 5 studies reporting RCTs ( Krudsood et al., 2007 ; Trung et al., 2009 ; Song et al., 2011 ; Thanh et al., 2012 ; Onasanya et al., 2015 ), and 2 reporting a noncomparative single-arm studies ( Deng et al., 2008 ; Wang et al., 2020 ) were included for the analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our initial search found 45 relevant articles published between 2000 and 2020, of which 9 reported repetitive data. After screening for titles, 38 abstracts, and 15 full-text reviewed, 5 studies reporting RCTs ( Krudsood et al., 2007 ; Trung et al., 2009 ; Song et al., 2011 ; Thanh et al., 2012 ; Onasanya et al., 2015 ), and 2 reporting a noncomparative single-arm studies ( Deng et al., 2008 ; Wang et al., 2020 ) were included for the analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, one was published in the Chinese language ( Deng et al., 2008 ) and others in the English language ( Krudsood et al., 2007 ; Trung et al., 2009 ; Song et al., 2011 ; Thanh et al., 2012 ; Onasanya et al., 2015 ; Wang et al., 2020 ). Four of the five RCTs ( Krudsood et al., 2007 ; Trung et al., 2009 ; Song et al., 2011 ; Thanh et al., 2012 ) and the two single-arm studies ( Deng et al., 2008 ; Wang et al., 2020 ) reported PCR-confirmed cure rate on day 28, while one trial reported the same on day 42 ( Onasanya et al., 2015 ). A total of 917 participants were included in the experiment, including 145 in the single-arm study, 335 in the AP group, 188 in the DHP group, 25 in the ASAM group, 59 in the ASAQ group, and 165 in the AL group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations